Penegakan Hukum Terhadap Pelanggaran Kode Etik Advokat - Giovani D.B. Nggabut; Adean E. Berti Bano; Damianus Bria; Kathrine M. Mamengko; Yuliiyana C.S. Mudamakin (Universitas Sains dan Teknologi Komputer, 2024)
Based on Article 33 of Law Number 18 of 2003 concerning Advocates, this code of ethics is declared mutatis mutandis to be valid until new provisions are made by the advocate organization. Considering that in Article 16 of Law Number 18 of 2003 concerning Advocates in conjunction with Constitutional Court decision No. 26/PUU-XI/2013 concerning Advocates, it is stated that: